Method of gamification in the system of continuing education - Zakharchuk, Maryana (Видавництво Львівської політехніки, 2017)
The article dwells on teaching foreign languages in the system of continuing education, as well as the method of gamification has been described as an alternative approach to learning in education of adults in the context of contemporary social development. The author has singled out the theoretical principles of learning necessary for foreign language learning and revealed their main ideas. The work of Linguistic and Educational Centre has been analyzed which was created to provide educational, methodological and consultative assistance to citizens, including scientists, teachers and students to study foreign languages.
Keywords: gamification; continuing education; adult education; language learning; educational principles